НАБЛЮДЕНИЕ ДВУХ КОРОНАЛЬНЫХ ВЫБРОСОВ МАСС 7 АПРЕЛЯ 2011 НА УРАН-2 - Мельник, В. Н.; Браженко, А. И.; Коноваленко, А. А.; Доровский, В. В.; Ващишин, Р. В.; Французенко, А. В.; Панченко, М.; Рукер, Г. (Одеські астрономічні публікації, 2011)
Two CME’s (coronal mass ejection) were registered by SOHO and STEREO on April 2, 2011. The results of observations obtained by radio telescope URAN-2 of different CME manifestations in radio emission at decameter wavelengths are discussed in this paper. Particularly it is reported about registration of new type of fine structure of type II bursts.